Pengaruh Reward dan Punishment dalam Kondisi Pandemi Covid-19 Terhadap Motivasi Kerja Serta Dampaknya pada Kinerja Karyawan PT XYZ - Olivia Rachelline Harlyanto; Ignatius Ario Sumbogo (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to find out the direct and indirect effects that arise from reward and punishment on work motivation and the partial impact on employee performance. Two exogenous variabels with one endogenous variabel and one intervening variabel were discussed using quantitative research with survei methods to 40 respondents at PT. XYZ with path analysis techniques. The results of the processed data show that reward and punishment variabels directly have a significant effect on employee motivation. The reward variabel does not directly affect employee performance, but punishment and work motivation variabels directly have a significant effect on employee performance. As well as the reward variabel indirectly affects the work motivation variabel on performance, but the punishment variabel does not affect indirectly through the work motivation variabel on employee performance.